Maturity as a Parameter of Readiness and Prevention of Early Marriage Risks: Medical and Sociological Review of Family Law - Bayu Dwi Prasetiawan; Azmi Siradjudin; Sakirman (Indonesian Journal of Islamic Law, 2024)
The problem that often occurs in early marriages is that they often experience arguments that stem from maturity issues. This has a huge effect on household harmony. Many young couples when faced with a problem, avoid it instead of solving it due to a lack of maturity. The researcher is a field researcher using a qualitative descriptive approach. This research was conducted in Punggur Subdistrict. The research findings are the parameters of women's maturity in family sociology, the age limit for marriage is 21 years for men and 18 years for women. Meanwhile, according to medical opinion, the maturity of women to marry by assessing the level of maturity of men and women to enter into marriage shows the age range above 20 years and above for women and 25 years for men. This is because getting married at the age of 20 in terms of health and psychological readiness is less risky, the fertility rate is higher and the eggs produced are good to reduce the risk of uterine cancer.